Alcohol and other substance abuse among youth: an obvious but neglected scenario in Shimla city of Himachal Pradesh, India - Kumar, Devender; Parashar, Anupam; Thakur, Anita (International Journal Of Community Medicine And Public Health, 2017)
Shimla, the former summer capital of the British in India, and the present capital of Himachal Pradesh, is the principal commercial, political and educational centre of the hilly regions of the state. For all these values, more than 1,60,000 people from different region of state are residing in urban area of Shimla.1 Moreover, thanks to its picturesque natural locales and pleasant climate it also attracts thousands of tourists every day. With due regards to all its importance, we want to highlight one rapidly growing social and public health problem in the city i.e. substance abuse. Substance abuse particularly among youth has become quite evident in the city in the form of alcohol, cigarette and other tobacco products, cannabinoid and opium extracts. Many contributing factors responsible for current scenario, which are being overlooked again and again, are described here as following.